I'll Try Anything Once : Using the Conceptual Framework of Children's Human Rights Norms in the United States - Dohrn, Bernardine (2007)
International human rights law provides norms, concepts, and standards of immediate and practical value to attorneys for court-involved children in the United States. The conceptual framework of the comprehensive rights of the child is broadly congruent with, or closely related to, the strongest aspects of US. constitutional law and practice. The expansive language of children's human rights offers an historic opportunity: new tools and a more comprehensive context in which to change how we think about young people in conflict with the law, children in state custody, and children in related legal settings. The challenge is to use these fresh substantive concepts as terms of reference in our work and our thinking, as a prelude and incentive to integrating the instructive nature of children's international law with the interpretation of our own laws and constitutional traditions. The adoption of the discourse itself can encourage and influence future implementation of enforceable domestic and international law that expands the rights and well-being of children